1998
DOI: 10.1007/s004250050354
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy-associated gene expression in pea axillary buds.

Abstract: Pea (Pisum sativum L. cv. Alaska) axillary buds can be stimulated to cycle between dormant and growing states. Dormant buds synthesize unique proteins and are as metabolically active as growing buds. Two cDNAs, PsDRM1 and PsDRM2, were isolated from a dormant bud library. The deduced amino acid sequence of PsDRM1 (111 residues) is 75% identical to that of an auxin-repressed strawberry clone. PsDRM2 encodes a putative protein containing 129 residues, which includes 11 repeats of the sequence [G]-GGGY[H][N] (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 28 publications
8
77
0
1
Order By: Relevance
“…amino acid sequence of the DRM1 gene in other species (Stafstrom et al, 1998;Kebrom et al, 2006). The DRM1-like gene was upregulated at 18 DAP in the third leaf axil in tin compared with wild-type buds, consistent with the conserved function of this gene and the dormancy status of the tin buds (Fig.…”
Section: Expression Of Tb1-and Drm1-like Genes In Axillary Buds Of Tisupporting
confidence: 65%
See 1 more Smart Citation
“…amino acid sequence of the DRM1 gene in other species (Stafstrom et al, 1998;Kebrom et al, 2006). The DRM1-like gene was upregulated at 18 DAP in the third leaf axil in tin compared with wild-type buds, consistent with the conserved function of this gene and the dormancy status of the tin buds (Fig.…”
Section: Expression Of Tb1-and Drm1-like Genes In Axillary Buds Of Tisupporting
confidence: 65%
“…SbMAX2 is a putative ortholog of Arabidopsis MAX2 and encodes an F-box protein, which probably functions in the perception or signal transduction of strigolactones (Stirnberg et al, 2002;Stirnberg et al, 2007). SbDRM1 is a putative ortholog of the DRM1 gene of pea that encodes a protein of unknown function (Stafstrom et al, 1998). Because the roles of MAX2 and DRM1 appear to be more closely aligned to dormancy than TB1, signal integration may occur downstream of TB1.…”
mentioning
confidence: 99%
“…In addition, the relative expression level in the mature tomato ovary of two genes homologous to PsDRM1, which proved to be excellent dormancy (DRM) markers in pea (Stafstrom et al 1998), are high. Together, this suggests that the mature ovary before pollination has entered a temporarily dormant state, during which the tissue is quiescent.…”
Section: Function Of Aba During Fruit Setmentioning
confidence: 99%
“…Gene expression and protein profiling studies in pea have revealed that removal of the shoot tip induces axillary buds to enter a transition state between dormancy and growth ( Fig. 2A) and that whether buds subsequently revert back to the dormant state or proceed to sustained growth is influenced by the state of other buds (Stafstrom et al, 1998;Shimazo-Sato and Mori, 2001).…”
Section: Vegetative Meristem Development Networkmentioning
confidence: 99%